The figure of vagrancy in the Rural Code of Buenos Aires (1856-1870) (Quinto Sol, 2011)
This work deals with a form of state intervention that affected the supply of rural labor, the persecution of vagrancy, a practice with a long tradition in the Pampa area, and which operated for social control for a long time. Specifically, we will analyse how it was considered in the Rural Code in the province of Buenos Aires (1865), where customs and new notions of law were embodied. How was vagrancy defined? How was it considered in the Rural Code? Is it possible to observe changes and continuities as regards the previous legislation? What debates did the inclusion in the Code, led to, before and after its passage? These are the main issues we attempt to tackle, through the analysis of sources relating to the creation of the rule from 1856 to 1870.
Keywords: state intervention; vagrancy; Rural Code; Rural Society